NEW MODEL OF SHARIA BANKING STRATEGY IN INDONESIA: KPPS ONLINE REPORT - Indra Gunawan, Cakti (Book of Open Source (BOS), 2025)
Indonesia, as one of the largest country in Asia, plays an important role in the development of the Asian economy and economic rotation. With a dense population and a country that has very promising economic potential, Indonesia has become one popular country in economic competition in Asian countries. An effort to improve the economy of a country, it is necessary to have financial institutions that can focus on managing the country's economic sector.